Pengembangan Modul Ajar Bahasa Indonesia Berbasis Penguatan Nilai P5-PPRA pada Kelas IV MI Datok Pattimang Kabupaten Luwu: Pengembangan Modul Ajar Bahasa Indonesia Berbasis Penguatan Nilai P5-PPRA pada Kelas IV MI Datok Pattimang Kabupaten Luwu - Alam Syahputera; Sukirman Nurdjan; Hisbullah Nurdin; Muhammad Guntur (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This study aims to develop an Indonesian Language Teaching Module by identifying the needs for developing an integrated teaching module that incorporates the values of P5-PPRA in the Indonesian language for fourth-grade students at MI Dato Pattimang. This research is a type of developmental research, commonly referred to as Research and Development (R&D). Research and Development is a research method used to develop and test products that will later be implemented in the educational field. There are various research models that can be used as references in this Research and Development study. The development model used in this research is ADDIE (Analyze, Design, Development, Implementation, Evaluation). This study is a type of research that can be used to develop learning products. Therefore, the research to be conducted uses a development approach to produce products that directly address problems found in the field while also improving the quality of education. The results of the study indicate that the feasibility of this teaching module, focusing on the Indonesian language, is assessed by design experts, material experts, and language experts. The evaluations from each validator state that this teaching module is very suitable for use by users, with improvements according to the experts' suggestions.